Relevance of HLA-DP/DQ and ICAM-1 SNPs among Ovarian Cancer Patients - Ghazy, Amany A.; El-Etreby, Nour M. (Frontiers in Immunology, 2016)
ABSTRACT: Background: Ovarian cancer is considered the most lethal gynecological malignancies and the fifth leading cause of cancer deaths among women. The high mortality rate is largely attributed to its diagnosis in advanced stages. Poor prognosis of ovarian cancer is usually due to lack of specific or effective screening and diagnostic methods for identifying early stage disease. Aim: Our study aimed to study the role of HLA-DP, HLA-DQ and ICAM-1 SNPs in diagnosis and/or prognosis of ovarian tumors. Subjects & methods: The current study was conducted on 60 patients with ovarian tumors (benign, borderline and malignant) and 20 healthy volunteers. Genotyping of HLA-DP rs 3077, HLA-DQ rs3920 and ICAM-1 rs1437 SNPs was done using 5' nuclease assay. Results: we found significant association of HLA-DP rs 3077 AA, HLA-DQ rs 3920 GG, ICAM-1 rs1437 CC and CT genotypes with increased risk of ovarian cancer (OR=43.5, 6, 25 and 2.6 respectively). In addition, HLA-DQ rs3920 and ICAM-1 rs1437 alleles vary significantly among different types of ovarian cancer (P=0.003 and 0.001, respectively). Conclusion: HLA-DP rs 3077, HLA-DQ rs3920 and ICAM-1 rs1437 SNPs could help in diagnosis and prognosis of ovarian cancer.